The National Adult Reading Test: restandardisation against the Wechsler Adult Intelligence Scale—Fourth edition. Issue 6 (18th August 2018) - Bright, Peter; Hale, Emily; Gooch, Vikki Jayne; Myhill, Thomas; van der Linde, Ian
ABSTRACT: Since publication in 1982, the 50-item National Adult Reading Test (NART; Nelson, 1982; NART–R; Nelson & Willison, 1991) has remained a widely adopted method for estimating premorbid intelligence both for clinical and research purposes. However, the NART has not been standardised against the most recent revisions of the Wechsler Adult Intelligence Scale (WAIS-III; Wechsler, 1997, and WAIS-IV; Wechsler, 2008). Our objective, therefore, was to produce reliable standardised estimates of WAIS-IV IQ from the NART. Ninety-two neurologically healthy British adults were assessed and regression equations calculated to produce population estimates of WAIS-IV full-scale IQ (FSIQ) and constituent index scores. Results showed strong NART/WAIS-IV FSIQ correlations with more moderate correlations observed between NART error and constituent index scores. FSIQ estimates were closely similar to the published WAIS and WAIS-R estimates at the high end of the distribution, but at the lower end were approximately equidistant from the highly discrepant WAIS (low) and WAIS-R (high) values. We conclude that the NART is likely to remain an important tool for estimating the impact of neurological damage on general cognitive ability. We advise caution in the use of older published WAIS and/or WAIS-R estimates for estimating premorbid WAIS-IV FSIQ, particularly for those with low NART scores.